Numerical simulation of temperature distribution and residual stress in TIG welding of stainless-steel single-pass flange butt joint using finite element analysis - Arora Hitesh; Kumar Rajeev; Gulati Piyush; Sharma Shubham; Dwivedi Shashi Prakash; Saxena Ambuj; Kumar Abhinav; Sharma Kuldeep; Kozak Dražan; Hunjet Anica; Abbas Mohamed (High Temperature Materials and Processes)
Controlling defects such as deformation in the weld joint and the residual or superfluous stresses due to tungsten inert gas (TIG) welding or arc welding is a major concern for many industries like aeronautical, automobiles, nuclear or atomic power plants, crude oil or fossil fuel industries where pipes are in use and circumferential welding is done. Arc welding is a metal joining process, and TIG welding is applied to many industrial sectors that require high-quality welding. Simulation has been done on single-pass TIG welding on the Flange pipe of SS316 to evaluate transient temperature, residual stresses, and distortion. First, a 3D model is developed and assembled in SolidWorks. Second, in an MSC Patran, preprocessing of the FE model is done. Finally, in MSC Marc, thermal and mechanical simulation is performed. Based on this simulation, the accuracy of welding of the flange–butt joint made of SS316 is validated. In this study, the information regarding simulation of temperature dispensation and residual or superfluous stresses is done on the flange–butt joint, and it found the stresses are compressive at the weld bead area, and along the transverse direction, stresses changed to the tensile. The experimental data show that the steep curve at 0.00 mm represents a maximum temperature near the weld path at approximately 2,352°C, and the slant curve shows the far away points from the weld path. Comparing it with FE analysis, the maximum temperature attained was around 2,539°C. An approximate deviation of 7.365% was observed. The results of the study will provide experimental and simulation analyses for the welding of pipes of stainless steel for the transportation of oil and gases in the petroleum industries.